Minimum Translation Modeling with Recurrent Neural Networks - Hu, Yuening; Auli, Michael; Gao, Qin; Gao, Jianfeng (European Chapter of the ACL (EACL), 2014)
We introduce recurrent neural network based Minimum Translation Unit (MTU) models which make predictions based on an unbounded history of previous bilingual contexts. Traditional back-off n-gram models suffer under the sparse nature of MTUs which makes estimation of high order sequence models challenging. We tackle the sparsity problem by modeling MTUs both as bags-of-words and as a sequence of individual source and target words. Our best results improve the output of a phrase-based statistical machine translation system rained on WMT 2012 French-English data by up to 1.5 BLEU, and we outperform the traditional n-gram based MTU approach by up to 0.8 BLEU.